Systemic reactions and anaphylaxis with an acute serum tryptase ≥14 μg/L: retrospective characterisation of aetiology, severity and adherence to National Institute of Health and Care Excellence (NICE) guidelines for serial tryptase measurements and specialist referral. Issue 7 (29th April 2014) - Srivastava, Sapna; Huissoon, Aarnoud P; Barrett, Victoria; Hackett, Scott; Dorrian, Susan; Cooke, Matthew W; Krishna, Mamidipudi T
Abstract : Aims: To characterise patients with systemic reactions and anaphylaxis with an acute serum tryptase of ≥14 μg/L against recently published World Allergy Organisation (WAO) diagnostic criteria. To also perform a clinical audit to assess adherence to National Institute of Health and Care Excellence (NICE) guideline recommendations regarding serial tryptase measurements and specialist referral. Methods: A systematic retrospective survey (2006–2010) was carried out (n=171; males=86; mean age±SD 48±20 years) and data were extracted from emergency department and specialist allergy clinic records. Results: 34 patients (20%) had a grade 1 reaction, 61 (36%) grade 2, 46 (27%) grade 3 and 6 patients (4%) grade 4 (24 patients (13%) could not be graded due to lack of adequate clinical details) and 6% developed a biphasic response. Serial tryptase measurements were not available in 117 (69%) of the cohort. 97 (57%) patients were referred for specialist assessment, and 72 (74%) attended. 50% of cases were diagnosed with idiopathic systemic reactions/anaphylaxis and 28%, 14% and 8% triggered by drugs, foods and other allergies including disorders of mast cell overload, respectively. A weak positive correlation was detected between acute serum tryptase and severity. Conclusions: The correlation between acute serum tryptase and severity of anaphylaxis/systemic reactions is weak. A significant proportion of patients with raised acute serum tryptase had mild reactions which did not meet WAO criteria for anaphylaxis and this may reduce the specificity of the test. The commonest aetiology in this cohort was idiopathic followed by drug and food allergies. NICE guidelines relating to serial tryptase measurements and specialist referral were not followed, and there is an urgent need to raise the awareness among clinicians involved in the management of anaphylaxis.